Notes on coherent polarization X-ray radiation by relativistic electrons in a crystal - Morokhovskii, V.L. (Вопросы атомной науки и техники, 2019)
This paper deals with restrictions on the use of so-called kinematical theory of coherent polarization X-ray radiation by relativistic electrons in a single crystal target. Розглянуто обмеження застосування так названої кінематичної теорії когерентного поляризаційного рентгенівського випромінювання релятивістських електронів в моно-кристалічній мішені. Рассмотрено ограниченя применимости так называемой кинематической теории когерентного поляризационного рентгеновского излучения релятивистских электронов в моно-кристаллической мишени.